THE NURSE AND THEIR ROLE IN HEALTH SITUATION ANALYSIS - Henrique Dias Guimarães, Mateus (Health and Society, 2023)
The nurse as a health manager requires knowledge of the health situation for the effective execution of their activities, identifying, describing, and explaining health problems found in their region. Once health needs are identified, priorities for actions will be determined. This is a literature review. The present study aims to address the importance of the nurse’s knowledge of the health situation for the implementation of planning practices and priority setting in health care. It is concluded that health data, obtained through the analysis of the health situation, are important for understanding the profile, generating appropriate care, and planning actions that guide and assist the population in a comprehensive and coercive manner.